Understanding delusion in dementia: A review. Issue 1 (23rd July 2013) - Cipriani, Gabriele; Danti, Sabrina; Vedovello, Marcella; Nuti, Angelo; Lucetti, Claudio
<x xml:space="preserve">Abstract</x> Alzheimer's disease and other dementia are associated with cognitive and functional impairment, as well as neuropsychiatric sequelae, including psychotic features. Research has largely concentrated on the study of cognitive decline, but the associated behavioral and neuropsychiatric symptoms are of equal importance in the clinical profile of the disease. Delusions are common, disabling and persistent in the course of dementia. The purpose of the present review was to examine the phenomenon of delusion in people with dementia. We searched the electronic databases for original research and review articles using the search terms "delusion, dementia, Alzheimer's disease, frontotemporal dementia, vascular dementia and Lewy body disease". Various types of explanations have been proposed regarding the etiology of delusional belief in dementia, and cerebral correlates are considered. Pharmacological and non‐pharmacological treatments are analyzed. Geriatr Gerontol Int 2014; 14: 32–39.